Carbon flux from bio-optical profiling floats: Calibrating transmissometers for use as optical sediment traps. (February 2017) - Estapa, Meg; Durkin, Colleen; Buesseler, Ken; Johnson, Rod; Feen, Melanie
Abstract: Our mechanistic understanding of the processes controlling the ocean's biological pump is limited, in part, by our lack of observational data at appropriate timescales. The "optical sediment trap" (OST) technique utilizes a transmissometer on a quasi-Lagrangian platform to collect sedimenting particles. This method could help fill the observational gap by providing autonomous measurements of particulate carbon (PC) flux in the upper mesopelagic ocean at high spatiotemporal resolution. Here, we used a combination of field measurements and laboratory experiments to test hydrodynamic and zooplankton-swimmer effects on the OST method, and we quantitatively calibrated this method against PC flux measured directly in same-platform, neutrally buoyant sediment traps (NBSTs) during 5 monthly cruises at the Bermuda Atlantic Time-series Study (BATS) site. We found a well-correlated, positive relationship (R 2 =0.66, n=15) between the OST proxy, and the PC flux measured directly using NBSTs. Laboratory tests showed that scattering of light from multiple particles between the source and detector was unlikely to affect OST proxy results. We found that the carbon-specific attenuance of sinking particles was larger than literature values for smaller, suspended particles in the ocean, and consistent with variable carbon: size relationships reported in the literature for sinking particles. We also found evidence for variability in PC flux at high spatiotemporal resolution. Our results are consistent with the literature on particle carbon content and optical properties in the ocean, and support more widespread use of the OST proxy, with proper site-specific and platform-specific calibration, to better understand variability in the ocean biological pump. Highlights: Optical sediment traps provide proxy observations of particle flux in the ocean. Settling particles have higher carbon-to-attenuation ratios than suspended particles. Well-calibrated, OSTs will broaden our observations of the biological carbon pump.